2007
DOI: 10.1007/s00018-007-7345-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis C virus internal ribosome entry site-mediated translation by an RNA targeting the conserved IIIf domain

Abstract: Hepatitis C virus (HCV) translation initiation depends on an internal ribosome entry site (IRES). We previously identified an RNA molecule (HH363-10) able to bind and cleave the HCV IRES region. This paper characterizes its capacity to interfere with IRES function.Inhibition assays showed that it blocks IRES activity both in vitro and in a human hepatoma cell line. Although nucleotides involved in binding and cleavage reside in separate regions of the inhibitor HH363-10, further analysis demonstrated the stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 32 publications
(58 reference statements)
1
57
2
Order By: Relevance
“…The resulting complexes were resolved in 5% native polyacrylamide gels in TB buffer (100 m m Tris–HCl pH 8.3, 86 m m boric acid) at room temperature. Gels were dried, scanned using a Storm 820 Phosphorimager (GE Healthcare, Little Chalfont, Buckinghamshire, UK) and analysed using Image Quant v.5.2 software (Molecular Dynamics, Sunnyvale, CA, USA) [26]. Dissociation constant ( K d ) values were calculated using Sigma Plot v.8.02 software (Systat Software Inc., San José, CA, USA) and adjusted with the equation y = ( B max x )/( K d + x ) as previously described [33], where y is the percentage of complexed aptamer, B max is the amplitude of the reaction, and x is the concentration of the substrate HCV‐CRE 194 RNA.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting complexes were resolved in 5% native polyacrylamide gels in TB buffer (100 m m Tris–HCl pH 8.3, 86 m m boric acid) at room temperature. Gels were dried, scanned using a Storm 820 Phosphorimager (GE Healthcare, Little Chalfont, Buckinghamshire, UK) and analysed using Image Quant v.5.2 software (Molecular Dynamics, Sunnyvale, CA, USA) [26]. Dissociation constant ( K d ) values were calculated using Sigma Plot v.8.02 software (Systat Software Inc., San José, CA, USA) and adjusted with the equation y = ( B max x )/( K d + x ) as previously described [33], where y is the percentage of complexed aptamer, B max is the amplitude of the reaction, and x is the concentration of the substrate HCV‐CRE 194 RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Among ribozymes tested in vitro were hammerhead constructs targeted at the apical loop of subdomain IIIb (HCV-195) 52, 53 or the subdomain IIIf (HH363). 5658 Conjugated chemical nucleases consisting of RNA-hydrolyzing imidazole derivatives tethered to guide oligonucleotides were shown to inhibit in vitro IRES-driven translation at sub-μM IC 50 values. 61 However, testing of the conjugates in HCV-infected cells suggested that the inhibition was due to the antisense effect of the guide oligonucleotide and not through cleavage by the attached imidazole.…”
Section: Strategies For Inhibition Of the Hcv Iresmentioning
confidence: 99%
“…Electrophoresis was performed at 4°C over 5 h at 15 mA in TBM buffer (45 mM TrisHCl at pH 8.3, 43 mM boric acid, and 0.1 mM MgCl 2 ). Gels were dried, scanned, and analyzed as previously described (Romero-Ló pez et al 2007). K d values were calculated using Sigma Plot 8.02 software according to the equation y = (B max x)/(K d + x) (PuertaFernández et al 2005), where y is the percentage of complexed inhibitory RNA, B max is the amplitude of the reaction, x is the concentration of the target RNA, and K d the dissociation constant.…”
Section: Binding Assaysmentioning
confidence: 99%